Recurrent chemotherapy-induced tumor lysis syndrome (TLS) with renal failure in a patient with chronic lymphocytic leukemia - successful treatment and prevention of TLS with low-dose rasburicase - Hummel, Margit; Buchheidt, Dieter; Reiter, Sebastian; Bergmann, Jörg; Adam, Katja; Hehlmann, Rüdiger (European journal of haematology, 2005)
Abstract: Introduction: Rasburicase is a recombinant urate oxidase that is produced by a genetically modified Saccharomyces cerevisiae and has been approved for prophylaxis and treatment of tumor lysis syndrome in 2001. In several studies, rasburicase, given at a dose of 0.15-0.2 mg/kg for up to 7 d, proved to be highly effective in lowering urate levels. Case report: We report the case of a patient with chronic lymphatic leukemia (CLL) who experienced tumor lysis syndrome (TLS) with acute renal failure after fludarabine/cyclophosphamide chemotherapy and after bendamustine treatment. During the first episode of TLS, after fludarabine/cyclophosphamide (creatinine 3.3 mg/dL, urate 24.6 mg/dL), the patient received rasburicase 0.2 mg/kg for 3 d. Urate levels decreased below the lower limit of normal and renal function recovered. After bendamustine therapy, given for disease progression 8 months later, TLS with acute oliguric renal failure re-occurred (creatinine 3.1 mg/dL, urate 20.8 mg/dL). The patient was treated with hyperhydration and two doses of rasburicase (0.056 mg/kg), resulting in a prompt decrease of the urate level and recovery of renal function. Both episodes of TLS were successfully treated with rasburicase in a lower dose than recommended by the manufacturer. During a second bendamustine course, TLS was successfully treated by low doses of rasburicase (0.056 mg/kg for 2 d). Conclusion: This is the first report of TLS in CLL after bendamustine chemotherapy reported in the literature. Treatment and prevention of TLS by low doses of rasburicase is possible and cost-effective.
Gesehen am 11.05.2022